2018
DOI: 10.1002/jhrm.21352
|View full text |Cite
|
Sign up to set email alerts
|

TeamSTEPPS®: An evidence‐based approach to reduce clinical errors threatening safety in outpatient settings: An integrative review

Abstract: The present review is consistent with marked improvement in communication, decrease in clinical error rates, and improvement in patient satisfaction. There is a significant need for evaluation of the impact of this validated toolkit from the Agency for Healthcare Research and Quality to maintain a sustainable health care environment for all stakeholders. As a result of this integrative review, a quality improvement project related to both the primary and secondary end points is in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 21 publications
(48 reference statements)
2
15
0
1
Order By: Relevance
“…These results agree with the results of the integrative review carried out by Parker et al 31 who reported that there was a significant reduction in clinical error rates and improvement in patient satisfaction after Team STEPPS implementation. Furthermore, Farup 32 reported there was a negative association between the patient safety culture and adverse medical events.…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with the results of the integrative review carried out by Parker et al 31 who reported that there was a significant reduction in clinical error rates and improvement in patient satisfaction after Team STEPPS implementation. Furthermore, Farup 32 reported there was a negative association between the patient safety culture and adverse medical events.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, most errors arose in documentation, regardless employees’ status on qualification, work experience, training and working hours. In addition to frequent error management trainings, a starting point might be to approach new, innovative documentation technologies, such as interactive tools for electronic documentation transfers as shown in a recent systematic review by Hanratty and colleagues (Hanratty et al., 2019), or to implement newly developed data registry systems for nursing‐sensitive indicators as presented in an investigation by Sim and colleagues (Sim et al., 2019) or similar toolkits as revealed in the evidence‐based study approach by Parker and colleagues (Parker et al., 2019) to ensure and increase patient safety in home care services.…”
Section: Discussionmentioning
confidence: 99%
“…The Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS®), developed by the U.S. Department of Defense (DOD) and the Agency for Healthcare Research and Quality (AHRQ) [3], is an evidence-based program contribute to improving quality and safety in health care. All these strategies and tools lead to promoting communication, reducing medical errors or adverse events, and improving patient satisfaction and outcomes [4].…”
Section: Introductionmentioning
confidence: 99%